2016
DOI: 10.18632/oncotarget.7126
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor GATA1 and the histone methyltransferase SET7 interact to promote VEGF-mediated angiogenesis and tumor growth and predict clinical outcome of breast cancer

Abstract: Angiogenesis is essential for tumor growth. Vascular endothelial growth factor (VEGF) is the most important regulator of tumor angiogenesis. However, how transcription factors interact with histone-modifying enzymes to regulate VEGF transcription and tumor angiogenesis remains unclear. Here, we show that transcription factor GATA1 associates with the histone methyltransferase SET7 to promote VEGF transcription and breast tumor angiogenesis. Using chromatin immunoprecipitation assay, we found that GATA1 was req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 49 publications
(56 reference statements)
2
43
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) is one of the most important regulators of tumor angiogenesis in breast cancer 34 . As Zhang Y. et al 35 reported that SET7/9, which is recruited by the transcription factor GATA1, can promote VEGF transcription and breast tumor angiogenesis. This evidence indicates that SET7/9 in breast cancer might function as an oncogene through the methylation of histones to activate target gene expression or the methylation of non-histone proteins directly.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is one of the most important regulators of tumor angiogenesis in breast cancer 34 . As Zhang Y. et al 35 reported that SET7/9, which is recruited by the transcription factor GATA1, can promote VEGF transcription and breast tumor angiogenesis. This evidence indicates that SET7/9 in breast cancer might function as an oncogene through the methylation of histones to activate target gene expression or the methylation of non-histone proteins directly.…”
Section: Discussionmentioning
confidence: 99%
“…PAK5-mediated GATA-1 phosphorylation regulates EMT in breast cancer cells. GATA-1 associates with the histone methyltransferase SET7 to promote VEGF transcription and breast tumor angiogenesis [31][32][33]. GATA-1 promotes cell proliferation, migration, and invasion via activating the PI3K/AKT signaling pathway in colorectal cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer patients, histone methyltransferase SET7 and transcription factor GATA1 expression levels were upregulated and positively correlated with VEGFA expression and microvessel number. Furthermore, SET7 associates with GATA1 to promote VEGFA transcription and breast tumor angiogenesis [125]. However, by using ProtoArray system, Cohn et al identified 172 new SETD3 interacting proteins, and further investigation found that SETD3 binds and methylates the transcription factor FoxM1 to inhibit VEGFA expression under hypoxia [126].…”
Section: Histone Methylation In Tumor Angiogenesismentioning
confidence: 99%